EFEKTIVITAS PENERAPAN PAY-FOR-PERFORMANCE PADA ASURANSI KESEHATAN DI NEGARA-NEGARA ASIA: LITERATURE REVIEW - Subur, Slamet; Rachmawaty, Rini; Saleh, Ariyanti (Universitas Tribhuwana Tunggadewi, 2022)
Public health insurance programs have become a global concern, especially in program planning such as resource use, knowing the effectiveness of pay-for-performance implementation in health insurance in Asian countries. Method Research design is a library study. Search for articles using the Pubmed, Ebsco, ScienceDirect, and Proquest databases. The research questions are structured using the PICO method, a database-based keyword search in MESH terms. Inclusion criteria are focused on the application of Pay-for-performance, on health insurance, applied in Asian countries, issued the last 10 years, in English. Found 748 articles, and only 9 articles were included according to research questions. Result: There are 9 articles included in this study. The results of a critical review of published articles, the application of pay-for-performance on health insurance in Asian countries improve the achievement of indicators, incentives and payment fines, and improve the quality of health services. Conclusion The application of Pay-For-Performance to health insurance in Asian countries is based on various indicators, payment systems, and improved quality of health services. Therefore, the application of Pay-For-Performance can be recommended for healthcare facilities in Asian countries.